2023
DOI: 10.1186/s12978-023-01620-0
|View full text |Cite
|
Sign up to set email alerts
|

Mistreatment of women during childbirth and its influencing factors in public maternity hospitals in Tehran, Iran: a multi-stakeholder qualitative study

Abstract: Background Mistreatment during labour and childbirth is a common experience for many women around the world. This study aimed to explore the manifestations of mistreatment and its influencing factors in public maternity hospitals in Tehran. Methods A formative qualitative study was conducted using a phenomenological approach in five public hospitals between October 2021 and May 2022. Sixty in-depth face-to-face interviews were conducted with a pur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
(66 reference statements)
0
7
2
Order By: Relevance
“…This project, initiated in October 2021, consists of five phases: (1) needs assessment, (2) identifying the interventions to reduce mistreatment of women during childbirth, (3) identifying the implementation challenges of interventions, (4) designing implementation strategies for the intervention, and (5) testing implementation strategies in a real-life setting. The results of phases 1 and 3 of the project are presented in detail elsewhere [ 5 , 27 , 28 ]. This study used an exploratory descriptive qualitative design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This project, initiated in October 2021, consists of five phases: (1) needs assessment, (2) identifying the interventions to reduce mistreatment of women during childbirth, (3) identifying the implementation challenges of interventions, (4) designing implementation strategies for the intervention, and (5) testing implementation strategies in a real-life setting. The results of phases 1 and 3 of the project are presented in detail elsewhere [ 5 , 27 , 28 ]. This study used an exploratory descriptive qualitative design.…”
Section: Methodsmentioning
confidence: 99%
“…Despite every woman’s right to have a positive birth experience, the mistreatment during childbirth has been documented worldwide in health facilities [ 1 4 ]. Recent studies from Iran have reported a high rate of mistreatment, including verbal abuse, frequent and painful vaginal examinations, neglect and abandonment, lack of supportive care, physical abuse [ 5 ], denial of mobility [ 5 – 7 ], and pain relief [ 5 , 8 ]. Additionally, women are typically not allowed to choose their labour positions [ 6 ] or have a birth companion [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The project was initiated in October 2021 in five public teaching hospitals in Tehran, Iran, and consists of five phases: (1) needs assessment (to assess knowledge, attitudes and practices of maternity healthcare providers about mistreatment of women during labour and childbirth, and the manifestations of mistreatment and its influencing factors), (2) identifying interventions to reduce mistreatment of women during childbirth, (3) identifying the implementation challenges of interventions, (4) designing implementation strategies for the intervention, and (5) testing implementation strategies in a real-life setting. The findings of phase 1 of the project are described elsewhere [ 11 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“… Presence of birth companions The possibility of presence of birth companions was provided by redesigning maternity wards to promote vaginal childbirth. However, most birth facilities do not provide birth companions [ 11 , 25 ]. Healthcare provider level Integrating RMC into in-service training of maternity staff In Iran, the first “congress on ethics in midwifery and reproductive health” with a focus on maternal dignity and the aim of increasing the knowledge, attitude, and behavioral intention of maternity hospital supervisors, was implemented at an online national workshop by the Ministry of Health and Medical Education (MOHME) in August 2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation